How South African brands in mainstream media portray the lived experiences of queer bodies - Hlabane, Atlegang (The IIE, 2022)
This research report examines how South African brands in mainstream media portray the lived experiences of queer bodies. Queer representation is impacted by debilitating tropes and beliefs that encourage damaging ideas regarding the LGBTQIA+ community. The purpose of this research study is to provide insight into how harmful and stereotypical queer representation can be damaging to queer people within society. The South African media fails to provide inclusive queer representation that validates the queer community. The objective is to describe the way the South African media portrays the lived experiences of queer bodies, this will allow marketers and other media personnel to understand the ramification of negative queer representation. The paper identifies and analyses different strategies used when portraying queer people. The intention of this paper is to build on previous research regarding queer representation, specifically within a South African perspective. The research report uses a qualitative approach, within an Interpretivist paradigm. The study is exploratory and makes use of a semiotic-visual content analysis using artefacts from lifestyle brands within the country. The research study revealed that the strategies commonly used to portray queer bodies and lived experiences, is based on a patriarchal perspective, where heterosexuality is placed above the queer community. This perspective perpetuates the use of sexualisation, objectification and the use of stereotypes that place the queer community and their experiences as a form of deviance. The focus of this study is one lifestyle brands, rather than all types of brands, which has proven to be a limitation within this study. The lack of a large array of artefacts to analyse contributes towards the limitations. This research report can prove to be beneficial to lifestyle brands in South Africa, by highlighting the strategies used to portray queer bodies that can be harmful, to avoid future advertising messages that are damaging towards the queer community.
Keywords: Body image; Stereotyping; Patriarchgy; Gender; Representation